2001
DOI: 10.1108/eb021182
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the contractor selection problem using an evidential reasoning approach

Abstract: Selecting the ‘best’ main contractor is a complex decision process for construction clients. It requires a large number of criteria to be simultaneously measured and evaluated. Many of these criteria are related to one another in a complex way and therefore, they very often conflict insofar as improvement in one often results in decline of another(s). Furthermore, as contractors' attributes are expressed in both quantitative and qualitative terms, decision‐makers have to base their judgements on both quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…To identify the real preferences of the decision makers, numerous hypothetical questions are asked from them which many times become a burden and consequently appear in the form of inconsistent results. The overall decision making procedure is lengthy and tedious, Customer experience in banks and with the increment in the number of criteria, the situation gets exacerbated (Sonmez et al, 2001). AHP, a multi-criteria decision making (MCDM) method can solve complex problems possessing both qualitative and quantitative parameters (Saaty, 1980).…”
Section: Selection Of Weighing Methodsmentioning
confidence: 99%
“…To identify the real preferences of the decision makers, numerous hypothetical questions are asked from them which many times become a burden and consequently appear in the form of inconsistent results. The overall decision making procedure is lengthy and tedious, Customer experience in banks and with the increment in the number of criteria, the situation gets exacerbated (Sonmez et al, 2001). AHP, a multi-criteria decision making (MCDM) method can solve complex problems possessing both qualitative and quantitative parameters (Saaty, 1980).…”
Section: Selection Of Weighing Methodsmentioning
confidence: 99%
“…The remarkable success of the approach can be attributed to resolution of the complexity of assessments of both qualitative and quantitative attributes with complete or incomplete original information. The step-by-step ER algorithm [12,18,24] is as follows.…”
Section: Evidential Reasoning Methodologymentioning
confidence: 99%
“…Yang [11] developed generic decision models with rule-as well as utility-based techniques for transforming information assessment in dealing with multipledecisions attribute analysis problems with both a quantitative type and a qualitative type of uncertainty. Examples of papers citing ER algorithms include references [12] to [17] and some diverse application-related papers are given in references [18] to [25]. Furthermore, recently published research investigations can be found in references [26] to [30].…”
Section: Introductionmentioning
confidence: 99%
“…It has established the fact that DST can allow an expression of partial knowledge [38] and Dempster's rule of evidence with overall Basic Probability Assignment (BPA) was combined successfully [34]. A notion of belief was applied to establish a decision maker's preference [39], and a decision model under uncertainty was discussed [40]. The degree of expectation can be considered as the measure of belief.…”
Section: Dempster-shafer Theory (Dst)mentioning
confidence: 99%